Gas-Liquid Flow in a Vertical Pipe Equipped with a Double Helical Swirl Separator Element - Ryan Anugrah Putra; Akhlisa Nadiantya Aji Nugroho; Aditya Ramadhona; Erick Wisnu Kuncoro Baroto (Jurnal Inotera, 2020)
Two different gas-liquid flow behavior downstream a double helical swirl element inside a vertical pipe was observed in our preliminary experiment. The present Computational Fluid Dynamics (CFD) study confirms that the dynamics of gas-liquid flows inside the swirl separator is highly influenced by the liquid superficial velocity. The separation behavior in this work at a liquid superficial velocity of 0.1 m/s was the worst both axially and radially since the gas core cannot be sustained up to the outlet. The separation condition was improved by the increase of the liquid superficial velocity. The best separation condition in this study was achieved at the liquid superficial velocity of 1.0 m/s where the dense gas core can be maintained up to the outlet.